2017
DOI: 10.1097/aud.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sensorineural Hearing Loss Using Various Transient-Evoked Otoacoustic Emission Stimulus Conditions

Abstract: Objectives An important clinical application of transient-evoked otoacoustic emissions (TEOAEs) is to evaluate cochlear outer hair cell function for the purpose of detecting sensorineural hearing loss (SNHL). Double-evoked TEOAEs were measured using a chirp stimulus, in which the stimuli had an extended frequency range compared to clinical tests. The present study compared TEOAEs recorded using an unweighted stimulus presented either at ambient pressure or tympanometric peak pressure (TPP) in the ear canal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The TEOAE results in the Normal group were similar to normal ears tested in Putterman et al (2017), who used the same TEOAE measurement system as in the present study. The relative absence of TEOAEs in the Otosclerosis and Surgery groups replicated past studies, and extended this feature to higher frequencies (5.7-8 kHz).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The TEOAE results in the Normal group were similar to normal ears tested in Putterman et al (2017), who used the same TEOAE measurement system as in the present study. The relative absence of TEOAEs in the Otosclerosis and Surgery groups replicated past studies, and extended this feature to higher frequencies (5.7-8 kHz).…”
Section: Discussionsupporting
confidence: 76%
“…The rationale for measuring TEOAEs with a chirp stimulus rather than a click stimulus is that, for the same total energy in the stimuli, the peSPL of the chirp is much lower than that of the click, for example, the peSPL of the chirp was 11.8 dB lower than that of the click in Keefe et al (2016). The chirp stimuli used in this study were identical to those used in Putterman et al (2017), for which the mean peSPL in normal adult ears was 76.4 dB. Because it is the peak levels that generate system distortion, the chirp stimulus is advantageous as it spreads out the energy in time, whereas a click stimulus concentrates the same energy in a brief time interval.…”
Section: Teoae Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In tandem with other studies (Putterman et al, 2017;Garinis et al, 2017) using the present measurements system, the present work extended pressurized measurements of TEOAEs in adult ears up to a stimulus frequency of 8 kHz, which allowed the study of pressurization effects at higher frequencies compared to previous studies (as reviewed in Sec. I, previous studies extended to 5 kHz).…”
Section: Teoae Methodsmentioning
confidence: 62%
“…Other studies have used the pressurized chirp TEOAE system described in the present work, although with less description of methodology. Putterman et al (2017) found that TEOAEs recorded at ambient and TPP conditions performed equally in classifying ears as having normal hearing or a sensorineural hearing loss. The inclusion criteria for their study was based on ages between 18 and 89 yrs, normal otoscopy, normal 226 Hz tympanometry including a TPP within 6100 daPa, and air-bone gaps of 10 dB or less between 0.5 and 4 kHz.…”
Section: Discussionmentioning
confidence: 91%